Aspergillus niger Spores Are Highly Resistant to Space Radiation - Cortesão, Marta; de Haas, Aram; Unterbusch, Rebecca; Fujimori, Akira; Schütze, Tabea; Meyer, Vera; Moeller, Ralf (Frontiers in Microbiology, 2020)
The filamentous fungus Aspergillus niger is one of the main contaminants of the International Space Station (ISS). It forms highly pigmented, airborne spores that have thick cell walls and low metabolic activity, enabling them to withstand harsh conditions and colonize spacecraft surfaces. Whether A. niger spores are resistant to space radiation, and to what extent, is not yet known. In this study, spore suspensions of a wild-type and three mutant strains (with defects in pigmentation, DNA repair and polar growth control) were exposed to X-rays, cosmic radiation (helium and iron-ions) and UV-C (254 nm). To assess the level of resistance and survival limits of fungal spores in a long-term interplanetary mission scenario, we tested radiation doses up to 1000 Gy and 4000 J/m2. For comparison, a 360-day round-trip to Mars yields a dose of 0.66 ± 0.12 Gy. Overall, wild-type spores of A. niger were able to withstand high doses of X-ray (LD90 = 360 Gy) and cosmic radiation (helium-ion LD90 = 500 Gy; and iron-ion LD90= 100 Gy). Drying the spores before irradiation made them more susceptible towards X-ray radiation. Notably, A. niger spores are highly resistant to UV-C radiation (LD90 = 1038 J/m2), which is significantly higher than that of other radiation-resistant microorganisms (e.g. Deinococcus radiodurans). In all strains, UV-C treated spores (1000 J/m2) were shown to have decreased biofilm formation (81 % reduction in wild-type spores). This study suggests that A. niger spores might not be easily inactivated by exposure to space radiation alone and that current planetary protection guidelines should be revisited, considering the high resistance of fungal spores.